SWOT Strategy Analysis of the Merger of Cigna Insurance Company with Chubb Life Company - Riduan, Muhammad; Anggraini, Tuti; Nasution, Juliana (Yayasan Sinergi Kawula Muda, 2024)
The merger is a strategic corporate move that aims to advance Chubb by expanding and strengthening its presence in Indonesia. But the fact is that after officially conducting a merger, a strategy is needed in facing future competition. The SWOT Strategy Analysis of this research was determined with the aim of business or identifying objects related to the research. The data used in this field research was collected and analyzed using qualitative methods. So that several objectives can be obtained in this study, namely the first objective is to provide new opportunities for companies to operate efficiently, while the second objective is to reduce costs and increase company efficiency after the merger. The results showed that Chubb Life Medan Branch has many opportunities that need to be utilized effectively. Therefore, the company should evaluate its existing resources, skills and weaknesses. Based on the analysis, this research can provide strategies to help Chubb Life Medan Branch collaborate with other companies. The findings suggest the implication that Chubb Life Medan Branch should focus on improving its internal environment and external environment to enhance its performance and competitiveness. In addition, one of the best methods to strengthen the company's base is through mergers. The argument is that mergers can enable businesses to achieve their goals more quickly.